Model Problem Based Learning pada Pembelajaran Al Islam di SMK Muhammadiyah 1 Batu - Anisatul Luthfia; Romelah Romelah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Education in schools, particularly in fiqh materials, often faces challenges in terms of student engagement and understanding. Fiqh, which is often perceived as rigid and theoretical, requires a more engaging and applicable approach to make it easier for students to grasp the concepts being taught. This study aims to describe the implementation of the Problem-Based Learning (PBL) model in Islamic Education at SMK Muhammadiyah 1 Batu and to analyze the impact of Problem-Based Learning (PBL) on students in Islamic Education learning. The PBL model was chosen due to its ability to enhance student understanding through problem-solving that is relevant to daily life. Using a case study method, this research collected data through observation, interviews, and documentation to assess the effectiveness of the Problem-Based Learning model in improving student comprehension. The results indicate that the use of the Problem-Based Learning model can increase students' interest and understanding of Islamic Education, especially in fiqh materials, although there are some technical challenges in its implementation.